2018
DOI: 10.1080/09273948.2018.1484495
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression among Patients with Uveitis and Ocular Inflammatory Disease at a Tertiary Center in Southern Thailand: Vision-Related Quality of Life, Sociodemographics, and Clinical Characteristics Associated

Abstract: Approximately one-tenth of our patients screened positive for anxiety and depression. Patients with poor understanding of their OID and poor self-reported visual function were at an increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The Thai version of HADS has been developed and tested (Nilchaikovit et al, 1996). The assessment has been commonly used in chronic non-communicable diseases (Hanprasertpong et al, 2017;Limampai et al, 2017;Sittivarakul & Wongkot, 2019). Our findings showed that the HADS assessment could be a useful tool to initially screen and monitor mental health of MDR-TB patients.…”
Section: Discussionmentioning
confidence: 76%
“…The Thai version of HADS has been developed and tested (Nilchaikovit et al, 1996). The assessment has been commonly used in chronic non-communicable diseases (Hanprasertpong et al, 2017;Limampai et al, 2017;Sittivarakul & Wongkot, 2019). Our findings showed that the HADS assessment could be a useful tool to initially screen and monitor mental health of MDR-TB patients.…”
Section: Discussionmentioning
confidence: 76%
“…This rate has varied between 8.1% and 54% in survey studies of patients with uveitis. 18,19,20,21,22 This wide range may be related to cultural differences, as well as the differences in disease activity, assessment tools used, and cut-off points specified in the studies. Maca et al 19 found that BDI scores were above the normal limit in 31.6% of the patients in their study of HLA-B27+ patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Thailand, which had the lowest reported rate of depression (8.1%), the authors attributed the low rate to cultural differences and their use of a different assessment tool. 22 The presence of chronic disease, bilateral involvement, oral corticosteroid use, and treatment with multiple immunomodulatory drugs have been shown to affect the rate of depression. 21 Onal et al 20 from Turkey reported a depression rate of 37.3% in patients with active uveitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies included patients with any type of ocular inflammatory disease which, though predominately made up of uveitis patients, also included patients with keratitis, mucous membrane pemphigoid, and scleritis. 38,46 Only one study specifically evaluated scleritis patients. Early studies primarily correlated recurrences of inflammation to self-reported patient stressors.…”
Section: Review Of the Literaturementioning
confidence: 99%